Prediction and observation of defect-induced room-temperature ferromagnetism in halide perovskites. (December 2020) - Sun, Zhiguo; Cai, Bo; Chen, Xi; Wei, Wenxian; Li, Xiaoming; Yang, Dandan; Meng, Cuifang; Wu, Ye; Zeng, Haibo
Abstract: The possibility to induce a macroscopic magnetic moment in lead halide perovskites (LHPs), combined with their excellent optoelectronic properties, is of fundamental interest and has promising spintronic applications. However, these possibilities remain an open question in both theory and experiment. Here, theoretical and experimental studies are performed to explore ferromagnetic states in LHPs originated from lattice defects. First-principle calculations reveal that shallow-level Br vacancies in defective CsPbBr3 can produce spin-splitting states and the coupling between them leads to a ferromagnetic ground state. Experimentally, ferromagnetism at 300 K is observed in room-temperature synthesized CsPbBr3 nanocrystals, but is not observed in hot-injection prepared CsPbBr3 quantum dots and in CsPbBr3 single crystals, highlighting the significance played by vacancy defects. Furthermore, the ferromagnetism in the CsPbBr3 nanocrystals can be enhanced fourfold with Ni 2+ ion dopants, due to enhancement of the exchange coupling between magnetic polarons. Room-temperature ferromagnetism is also observed in other LHPs, which suggests that vacancy-induced ferromagnetism may be a universal feature of solution-processed LHPs, which is useful for future spintronic devices.